Physical and Mental Health Status of Adolescents of Government Juvenile Development Centers in Bangladesh (Bangladesh Medical Journal, 2019)
Gradual rising of crime among adolescents is now a social and public health concern worldwide. A total of 1.9 million children getting incarcerated worldwide yearly where in Bangladesh, 1.3 million of children engaged in hazardous job most of them involved in crime. Again, physical and mental well-being is the legal and constitutional rights of the every adolescent including detained adolescent of Juvenile Development Centers. This is a cross-sectional study conducted to assess the physical and mental health status as well as socio-demographic status of adolescents of two Government Juvenile Development Center, Tongi and Konabari, Gazipur from January to December 2017. 191 adolescents were selected purposively (male: female=1.41:1). Data were collected by face to face interview and record review and height and weight of the respondents were measured. The mental health status was measured by WHO-5 Well-being Scale. The age range was from 13 to 17 years. Age of the respondents were significantly correlated with score of the WHO-5 well-being scale (p=0.028). The study observed higher score among respondents who had detained here for more than 2 months which was highly significant (p